2014
DOI: 10.3389/fgene.2014.00174
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Schistosoma mansoni Y-box-binding protein (SMYB1) potential as a vaccine candidate against schistosomiasis

Abstract: Schistosomiasis is a neglected tropical disease, and after malaria, is the second most important tropical disease in public health. A vaccine that reduces parasitemia is desirable to achieve mass treatment with a low cost. Although potential antigens have been identified and tested in clinical trials, no effective vaccine against schistosomiasis is available. Y-box-binding proteins (YBPs) regulate gene expression and participate in a variety of cellular processes, including transcriptional and translational re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…SMYB1 has been verified the ability to bind DNA and RNA like other Y‐box proteins and may act in the process of RNA metabolism . Furthermore, mice immunized with the recombinant SMYB1 (rSMYB1) were detected the high levels of specific anti‐rSMYB1 antibodies in their sera . SJYB1 reported in our study shares 83.33% identity in its nucleotide sequence and 94.47% in its protein sequence with SMYB1 (data not shown).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…SMYB1 has been verified the ability to bind DNA and RNA like other Y‐box proteins and may act in the process of RNA metabolism . Furthermore, mice immunized with the recombinant SMYB1 (rSMYB1) were detected the high levels of specific anti‐rSMYB1 antibodies in their sera . SJYB1 reported in our study shares 83.33% identity in its nucleotide sequence and 94.47% in its protein sequence with SMYB1 (data not shown).…”
Section: Discussionmentioning
confidence: 64%
“…Recombinant SJYB1 inhibited the expression of collagen type I, but not α‐SMA in LX‐2 cells, suggesting that rSJYB1 specifically regulates synthesis of collagen type I rather than HSC activation. Unexpectedly, another study on mice infected with S mansoni has revealed that infected mice immunized with rSMYB1 exhibited reductions in the number of adult worm and eggs/granuloma retained in the liver, but no significant decrease was detected in the area of fibrosis . It is possible that the roles of YB1 from schistosomes in vitro are not entirely consistent with that in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, in 2014, publications from three Brasilian groups reported protection against schistosome challenge after vaccination of mice using what are unquestionably intracellular proteins. The four proteins were Syntenin [ 1 ], Dynein light chains DLC12 and DLC13 [ 2 ], and Y box protein [ 3 ]. Secondly, we undertook a quantitative shotgun proteomic analysis of the ubiquitous antigen preparation SWAP, the soluble cytosolic extract of adult worms [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is still a lack of agreement on the type of immune response that needs to be induced by a vaccine candidate to achieve a satisfactorily high degree of protection against schistosome infection (Dias et al , 2014). The cellular Th1 profile characterized by an increase in IFN-γ has been shown to be more effective in preventing experimental schistosomiasis, although a strong Th2 or a mixed Th1/Th2 response was associated with reducing the worm burden (Rofatto et al , 2013).…”
Section: Introductionmentioning
confidence: 99%